Assessment of the lean production effect on the sustainable industrial enterprise development - Dakov, Ivan; Novkov, Svetoslav (Business: Theory and Practice, 2007)
Most of the industrial enterprises, aimed at perfection through continuous improvement of their competitiveness and sustainability, deeply analysing the existing opportunities, focus their attention mainly on efficiency improvement. Taking into account this fact, in the present article more attention is paid to the evolutionary approach for enterprise development and the lean idea. Having in mind the results of analyses concerning the use of lean production as a step to sustainability and the sustainability reporting practices of the leading industrial enterprises, a short set of indicators is offered for assessing the lean production effect on the sustainable industrial enterprise development.